Preparation of PZT Thin Film/Ni Particle Composite Magnetoelectric Materials. Issue 1 (March 2020) - Di, Yongjiang; Chen, Sijing; Jiang, Yang; Jia, Bi; Cao, Pengjun
Abstract: Lead Zirconium Titanate (PZT) thin film magnetoelectric materials have widely application in controllable sensing and tuneable microwave devices. The PZT film ferroelectric domain was designingly distributed and reversed by using the piezoelectric power response technique. The magnetoelectric composite of PZT film and Ni particle was prepared by the ferroelectric spontaneous polarization separation photogenerated carrier, reduction Ni atom deposition on the PZT thin film ferroelectric positive domain region. The optical morphology, XRD and SEM morphology show that the Ni particles deposited on the PZT film increase first and then become more uniform with the extension of deposition time. The deposition time closely relate to the deposition effect of Ni particles, and the deposition effect is more obvious with time. After the photo-deposition, the surface particles of the unexcited domain film are scattered after the photo-deposition, and the shape of the deposited particles region in which the Ni particles are reduced is substantially similar to the write-domain pattern, and the particle diameter is about 10-20 nm.